The snakehead retrovirus promoter functions independently of the 3'ORF protein and its products are maternally inherited in transgenic zebrafish. - Rachel Zamostiano; Odelia Pisanty; Japhette Esther Kembou-Ringert; Reem Abu Rass; Avi Eldar; Marcelo Ehrlich; Yoav Gothilf; Eran Bacharach (PLoS Pathogens)
The exogenous snakehead retrovirus (SnRV) is an unclassified member of the Orthoretrovirinae subfamily, discovered in cell lines derived from several fish species. SnRV resembles complex lentiviruses and potentially encodes accessory proteins, including the product of the 3' open reading frame (3'ORF). The 3'ORF protein was suggested to function as a transactivator of transcription (Tat). Here, we constructed an infectious molecular clone for SnRV and tested the effects of 3'ORF mutations on SnRV transcription. Although replacing 3'ORF with foreign sequences strongly reduced virus expression and production, an out-of-frame point mutation in 3'ORF had only a minimal effect on SnRV replication. This latter result suggests that the 3'ORF protein does not function as Tat and that SnRV transcription is largely independent of the product of this ORF. We also show that in vitro, the SnRV promoter is versatile and robustly functioning in both fish and mammalian cultured cells. Finally, the SnRV promoter was transiently active in injected zebrafish embryos as early as the blastula stage. In transgenic zebrafish, this promoter drives enhanced expression in sensory organs and gonads, and its generated products are maternally inherited. Considering these characteristics, the SnRV promoter emerges as a promising candidate for developing versatile expression vectors applicable to research and biotechnological applications.